2021
DOI: 10.3390/biom11081090
|View full text |Cite
|
Sign up to set email alerts
|

Suppressive Effects of Rosmarinic Acid Rich Fraction from Perilla on Oxidative Stress, Inflammation and Metastasis Ability in A549 Cells Exposed to PM via C-Jun, P-65-Nf-Κb and Akt Signaling Pathways

Abstract: Particulate matter from forest fires (PMFF) is an environmental pollutant causing oxidative stress, inflammation, and cancer cell metastasis due to the presence of polycyclic aromatic hydrocarbons (PAHs). Perilla seed meal contains high levels of polyphenols, including rosmarinic acid (RA). The aim of this study is to determine the anti-oxidative stress, anti-inflammation, and anti-metastasis actions of rosmarinic acid rich fraction (RA-RF) from perilla seed meal and its underlying molecular mechanisms in A549… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(16 citation statements)
references
References 103 publications
0
13
0
Order By: Relevance
“…In monocyte subsets, there had basal expression of COX-2 and 5-LOX, and the expression increased significantly after stimulation with purified protein derivative (PPD) of Mycobacterium tuberculosis [ 82 ]. Recent evidence display that upregulation of COX-2 promotes tumorigenesis by promoting the metastasis signal affecting MMP-9 activity, it attenuates cancer cell migration and invasion via Akt, NF-Κb, and AP-1 signal pathways [ 83 ]. In addition to affecting tumor metastasis, upregulation of COX-2 is correlated with inhibition of apoptosis and increased intratumoral microvessels growth [ 84 – 86 ].…”
Section: Cox-2 Of Pulmonary Tuberculosis and Lung Cancermentioning
confidence: 99%
“…In monocyte subsets, there had basal expression of COX-2 and 5-LOX, and the expression increased significantly after stimulation with purified protein derivative (PPD) of Mycobacterium tuberculosis [ 82 ]. Recent evidence display that upregulation of COX-2 promotes tumorigenesis by promoting the metastasis signal affecting MMP-9 activity, it attenuates cancer cell migration and invasion via Akt, NF-Κb, and AP-1 signal pathways [ 83 ]. In addition to affecting tumor metastasis, upregulation of COX-2 is correlated with inhibition of apoptosis and increased intratumoral microvessels growth [ 84 – 86 ].…”
Section: Cox-2 Of Pulmonary Tuberculosis and Lung Cancermentioning
confidence: 99%
“…After extracting oil from the seeds, RA can be enriched by 70% ethanol and ethyl acetate extraction. The RA-enriched fraction reduced reactive oxygen species (ROS) and inhibited invasion through the NF-κB pathway in A549 cells [ 21 , 22 ].…”
Section: Culture Techniques Extraction Processes and Anti-tumor Appli...mentioning
confidence: 99%
“…One of the specific mechanisms by which the PI3K/Akt pathway promotes tumorigenesis is through the dysregulation of inflammatory mediators and immunity. It has been shown that rosmarinic acid subsequently prevents lung tumor invasion by reducing the production of inflammatory factors, such as IL-6, IL-8, TNF-α and cyclooxygenase-2, by inhibiting Akt phosphorylation ( 26 ). We speculate that this mechanism of action of the PI3K/Akt pathway is equally applicable during the pathogenesis of digestive tumors.…”
Section: Regulation Of Inflammationmentioning
confidence: 99%
“…Abnormal lipid metabolism leads to disturbances in adipokine secretion, which is strongly associated with tumorigenesis and tumor progression ( 41 ). Obesity due to abnormal lipid metabolism is an independent risk factor for tumorigenesis and tumor development in a variety of liver, pancreatic, ovarian and colorectal cancer types ( 26 , 40 , 42 ). The role of CTRP6 in glycolipid metabolism has been extensively studied ( 43 ).…”
Section: Regulation Of Glycolipid Metabolismmentioning
confidence: 99%